Faculty and Advisor Advice for Cybersecurity Students: Liberal Arts, Interdisciplinarity, Experience, Lifelong Learning, Technical Skills, and Hard Work - Brian K. Payne; Bria Cross; Tancy Vandecar-Burdin (Journal of Cybersecurity Education, Research & Practice)
The value of academic advising has been increasingly emphasized in higher education. In this study, attention is given to the most significant types of advice that a sample of cybersecurity faculty and advisors from the Commonwealth of Virginia recommend giving to cybersecurity students. The results show that faculty and advisors recommended that students be aware of six different aspects of cybersecurity education including the value of experience, the need for lifelong learning, the importance of hard work, the need to develop technical skills, the interdisciplinary nature of cybersecurity, and the need to develop liberal arts or professional/soft skills. Implications of the findings include the need to embrace the advising of cybersecurity students, the importance of helping cybersecurity faculty and advisors deliver effective advising, and recognition that good advising is more than simply telling students which classes to take.